Disseminated histoplasmosis presenting with chronic ulcerative tongue lesions in a patient with diabetes - Hasmoni, Mohamed Hadzri; Mohd Shah, Azarisman Shah; Ayoub, Suhaimi; Lau, Shin Hin; Abdul Rashid, Mohd Amran (BMJ Publishing Group, 2010)
We describe a case of chronic tongue ulceration with systemic symptoms in a patient with poorly controlled diabetes. A biopsy of a lesion from the posterior third of the tongue showed features typical of histoplasmosis. A CT of the thorax and abdomen revealed a diffuse reticulonodular pattern bilaterally.The intra-abdominal organs were normal.